2018
DOI: 10.1590/0103-6513.20170099
|View full text |Cite
|
Sign up to set email alerts
|

The use of ICT tools to support collaborative product development activities: evidences from Brazilian industry

Abstract: Paper aims: This paper aims to understand the relationship between Information & Communication Technology (ICT), collaborative New Product Development (NPD) and customer satisfaction (NPD performance). Originality: We target the relationship between ICT, collaborative NPD and NPD performance. ICT is assessed as a set of specific tools adopted by the companies. Research method: We test the mediating role of collaborative practices in the effect of ICT tools on customer satisfaction (as NPD performance) by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 89 publications
(147 reference statements)
0
11
0
3
Order By: Relevance
“…-External involvement in new product development Specific studies involving the integration of diverse stakeholders in new product projects-such as customers, suppliers, and universities-have also drawn the attention of researchers involved with the OI field (Bueno & Balestrin, 2012;Enrique et al, 2018;González & Toledo, 2012;Reame Junior & Amaral, 2012;Mazini et al, 2013;Merino et al, 2018). Using the simulation method to analyze relations between new product development and OI, Merino et al (2018) verified that the generation and absorption of external knowledge and entry of new competitors can accelerate the innovation process, which tends to promote differentiation of value for the consumer and greater visibility of the product in the market.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-External involvement in new product development Specific studies involving the integration of diverse stakeholders in new product projects-such as customers, suppliers, and universities-have also drawn the attention of researchers involved with the OI field (Bueno & Balestrin, 2012;Enrique et al, 2018;González & Toledo, 2012;Reame Junior & Amaral, 2012;Mazini et al, 2013;Merino et al, 2018). Using the simulation method to analyze relations between new product development and OI, Merino et al (2018) verified that the generation and absorption of external knowledge and entry of new competitors can accelerate the innovation process, which tends to promote differentiation of value for the consumer and greater visibility of the product in the market.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Reame Junior & Amaral (2012) observed that factors such as trust, commitment, documented learning, team continuity, and good relationship are key elements for the good performance of these collaborative relationships in new product development projects. Enrique et al (2018) noted that information and communication technology tools are important to support collaborative practices between different partners in new product development processes, because these boost communication and cooperation in these kinds of projects.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Knowledge sharing with external suppliers is a key factor for the NDP success (Petersen et al, 2005;Ayala et al, 2017;Enrique et al, 2018). Many authors contributed in expanding the understanding about how knowledge flows among individuals and organizations.…”
Section: Knowledge Sharing In Npdmentioning
confidence: 99%
“…Considering the increasing need of multidisciplinary knowledge for the successful of NPD, there is a growing need of collaboration both internally and externally (Enrique et al, 2018). As stated by Enrique et al (2018), external partnership includes several distinct actors, such as customers, suppliers, universities and research institutes, and even competitors, being suppliers and customers are the most common ones.…”
Section: Collaboration Between Organizationsmentioning
confidence: 99%
See 1 more Smart Citation